2012
DOI: 10.3164/jcbn.11-74
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin prevents changes in the activities of thioredoxin reductase and paraoxonase in hypercholesterolemic rabbits

Abstract: This study explored the effects of the antioxidant astaxanthin on paraoxonase and thioredoxin reductase activities as well as on other oxidative stress parameters and on the lipid profile in hypercholesterolemic rabbits. Rabbits were fed a standard or a hypercholesterolemic diet alone or supplemented with 50, 100 and 500 mg/100 g of astaxanthin for 60 days. Antioxidant enzymes activities, lipid profile and oxidative stress markers were evaluated in the serum. The hypercholesterolemic diet increased lipids, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…It has been widely used as a functional additive in aquaculture, mostly as exogenous pigment and antioxidant (Choubert, Cravedi, & Laurentie, ; Ingle de la Mora, Arredondo‐Figueroa, Ponce‐Palafox, Barriga‐soca, & Vernon‐Carter, ; Page & Davies, ; Ytrestoyl & Bjerkeng, ). The regulating effects of ASTX on lipid metabolism have been reported in terrestrial animals (Aoi et al, ; Bhuvaneswari, Arunkumar, Viswanathan, & Anuradha, ; Jia et al, ; Jia, Wu, Kim, Kim, & Lee, ; Kimura et al, ; McCarty, ), which suggested that ASTX has high potential to lower the lipid accumulation in plasma, liver and adipose tissue, although there were also contradictory results in some studies (Augusti et al, ; Kim et al, ; Ursoniu, Sahebkar, Serban, & Banach, ). ASTX has even been considered to be a candidate for preventing the development of nonalcoholic fatty liver disease (Yang et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…It has been widely used as a functional additive in aquaculture, mostly as exogenous pigment and antioxidant (Choubert, Cravedi, & Laurentie, ; Ingle de la Mora, Arredondo‐Figueroa, Ponce‐Palafox, Barriga‐soca, & Vernon‐Carter, ; Page & Davies, ; Ytrestoyl & Bjerkeng, ). The regulating effects of ASTX on lipid metabolism have been reported in terrestrial animals (Aoi et al, ; Bhuvaneswari, Arunkumar, Viswanathan, & Anuradha, ; Jia et al, ; Jia, Wu, Kim, Kim, & Lee, ; Kimura et al, ; McCarty, ), which suggested that ASTX has high potential to lower the lipid accumulation in plasma, liver and adipose tissue, although there were also contradictory results in some studies (Augusti et al, ; Kim et al, ; Ursoniu, Sahebkar, Serban, & Banach, ). ASTX has even been considered to be a candidate for preventing the development of nonalcoholic fatty liver disease (Yang et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…[42] Because the modulation of the cellular redox balance is critically important in the pathogenesis of cardiovascular disorders and the TRx system exerts important protective roles against ROS, it seems likely that TRxR is a promising target for clinical therapy of CVD. [33,43] In this study, the treatment with (PhSe)2 increased TRxR activity in the heart homogenates of young adult LDLr −/− mice. Of particular therapeutic significance, (PhSe)2 can mimic the endogenous antioxidant enzyme GPx or can be metabolized by TRxR into selenol intermediates that can imitate the function of the antioxidant selenoenzymes, which favour the cardiovascular redox state.…”
Section: Discussionmentioning
confidence: 59%
“…57 And also Reduces cardiovascular diseases. 58 Nutraceuticals and functional foods are used in the control of plasma cholesterol levels. 59 A variety of antioxidant compounds derived from natural products (nutraceuticals) have demonstrated neuroprotective activity in either in vitro or in vivo models of neuronal cell death or neurodegeneration.…”
Section: Temperature Effectmentioning
confidence: 99%